B cell depletion: a novel therapy for autoimmune diabetes? - Bour-Jordan, Hélène (American Society for Clinical Investigation, 2007)
Autoimmune diabetes is believed to be mediated primarily by T cells. However, B cells have been implicated in the pathogenesis of the disease in NOD mice. Although preclinical studies have been limited by the absence of anti-CD20 reagents that can induce B cell depletion in mice, a clinical trial using the B cell–depleting anti-CD20 monoclonal antibody rituximab (Rituxan) is underway in type 1 diabetes patients. In this issue of the JCI, Hu et al. describe the generation of transgenic NOD mice that express human CD20 on B cells (see the related article beginning on page 3857). They show that anti-CD20 therapy induces B cell depletion in these mice and offers some level of protection against diabetes. Although many questions remain unanswered, this mouse model represents the first opportunity to evaluate the potential value of rituximab as a novel therapy for autoimmune diabetes.